Evaluating the Effectiveness of Undergraduate Translation Technology Training in China (International Journal of Language, Literacy and Translation, 2025)
Translation technology plays an indispensable role in the global language services industry. As a key component of modern translation pedagogy, translation technology training has been widely integrated into tertiary translation programs in China. However, the effectiveness of undergraduate translation technology training remains underexplored. To address this gap, an online questionnaire survey was conducted with 309 undergraduate students to investigate their perceptions of translation technology training. Kaufman’s model was adapted and used as the framework to evaluate the training's effectiveness. The results indicate that over half of the students expressed a positive attitude toward translation technology training. Most students found it effective in helping them acquire procedural knowledge of translation technology and enhance their overall technological competence. However, some students raised concerns about the availability of resources, insufficient hands-on practice, and the limited duration of training. The study concludes that undergraduate translation technology training requires increased resource investment, an extended training duration, and a stronger emphasis on fostering students’ autonomy. These findings contribute to a deeper understanding of how to enhance undergraduate translation technology training in similar contexts and provide a reference for future program development.